Different ecological strategies during the seed germination phase of nine grasses inhabiting the hyper‐arid Arabian desert. Issue 4 (23rd August 2018) - Bhatt, Arvind; Santo, Andrea
Abstract: The effect of photoperiod, thermoperiod and their interaction on seed germination and its rate was studied for nine grasses growing in the Arabian desert. Germination tests were conducted under two photoperiods and three thermoperiods. Germination of light‐incubated seeds of Hyparrhenia hirta, Pennisetum divisum, Stipacapensis, Centropodia forsskaolii, Stipagrostis plumosa, Cymbopogon parkeri and Panicum turgidum was significantly higher than that detected in the darkness. Photoperiod did not influence the seed germination of Aristida adscensionis and Imperata cylindrica . Seeds of all species, except P. divisum, C. parkeri and I. cylindrica, germinated indepen dently of the tested temperature. Our results indicate that species belonging to the same family and growing in the same hyper‐arid desert habitat may influence and act in different ways during the seed germination phase, causing species‐specific effects, and therefore might affect the ecology of each taxon in this harsh environment. Abstract : The effect of photoperiod, thermoperiod and their interaction on seed germination and its rate was studied for nine grasses growing in the Arabian desert. Our results indicate that although these species belongs to the same family and grows in similar hyper‐arid desert habitat environmental conditions, the effect of temperature and light may influence and act in different ways during the seed germination phase, causing species‐specific effects, and therefore might affect the ecology of each taxon in this harsh environment.